Corydaline alleviates Parkinson's disease by regulating autophagy and GSK-3β phosphorylation. - Zhou, Kaikai; Xu, Shasha (Psychopharmacology, 2024)
Background: Jitai tablet, a traditional Chinese medicine, has a neuroprotective effect on 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-induced Parkinson's disease (PD) mice. As one of the main active ingredients in the Jitai tablet, corydaline (Cory) has analgesic and anti-allergic effects, but it has not been studied in PD. Here, we investigated the role and mechanism of Cory in PD. Methods: The PD model was induced by MPTP. Cell viability was measured by 3-(4, 5)-dimethylthiahiazo (-z-y1)-3, 5-di-phenytetrazoliumromide assay. The Pole test and traction test were performed to detect the behaviors of mice. The expression of tyrosine hydroxylase (Th) was detected by immunohistochemistry and Western blot. Immunofluorescence staining, monodansylcadaverine staining, and Western blot were conducted to assess autophagy. A lactic dehydrogenase release assay was used to detect cytotoxicity. Network pharmacology was used to screen the targets. Results: There existed cytotoxicity when the concentration of Cory reached 40 μg/mL. Cory (not exceeding 20 μg/mL) could alleviate MPTP-induced cell damage. In vivo experiments indicated that Cory could improve the motor coordination of mice with PD. Besides, Cory could increase LC3-II/LC3-I levels both in vivo and in vitro. In addition, the Th levels reduced in the striatum and middle brain tissues of Parkinson's mice were recovered by Cory injection. We also found that Cory decreased the phosphorylation of glucogen synthase kinase-3 beta (GSK-3β) at Tyr216 and increased the phosphorylation of GSK-3β at Ser9 not only in primary neurons and SH-SY5Y cells but also in the striatum and middle brain tissues. Furthermore, Cory increased LC3-II/LC3-I levels and decreased p62 levels by regulating GSK-3β. Conclusion: Cory enhanced autophagy, attenuated MPTP-induced cytotoxicity, and alleviated PD partly through the regulation of GSK-3β phosphorylation.